2010
DOI: 10.1007/s00262-010-0822-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II trial of personalized peptide vaccine plus low dose estramustine phosphate (EMP) versus standard dose EMP in patients with castration resistant prostate cancer

Abstract: Personalized peptide vaccination (PPV) combined with chemotherapy could be a novel approach for many cancer patients. In this randomized study, we evaluated the anti-tumor effect and safety of PPV plus low-dose estramustine phosphate (EMP) as compared to standard-dose EMP for HLA-A2- or -A24-positive patients with castration resistant prostate cancer. Patients were randomized into groups receiving either PPV plus low-dose EMP (280 mg/day) or standard-dose EMP (560 mg/day). After disease progression, patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(133 citation statements)
references
References 25 publications
6
127
0
Order By: Relevance
“…As the peptides were injected s.c. vaccines were well tolerated and showed reactivity (DTH-reactions, CTL and IgG responses) and clinical activity (PSA declines up to 30 % in four out of 17 patients . In a second trial the combination with estramustine showed a better PFS as estramustine alone (p < 0.05) (Noguchi et al, 2010).…”
Section: Other Dna-vaccinesmentioning
confidence: 99%
“…As the peptides were injected s.c. vaccines were well tolerated and showed reactivity (DTH-reactions, CTL and IgG responses) and clinical activity (PSA declines up to 30 % in four out of 17 patients . In a second trial the combination with estramustine showed a better PFS as estramustine alone (p < 0.05) (Noguchi et al, 2010).…”
Section: Other Dna-vaccinesmentioning
confidence: 99%
“…We developed a new approach of peptide-based vaccination, named personalized peptide vaccination (PPV), in which vaccine antigens are selected and administered based on preexisting host immunity before vaccination (6)(7)(8)(9)(10)(11)(12)(13)(14). We have shown promising results of PPV in various types of advanced cancers (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown promising results of PPV in various types of advanced cancers (6)(7)(8)(9). For example, a recently conducted randomized clinical trial of PPV for patients with advanced prostate cancer suggested a potentially favorable clinical outcome in the vaccinated group (9). However, to improve clinical efficacy further, prognostic biomarkers that would make it possible to select patients for whom cancer vaccines would be appropriate remain to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…17 In the clinical trials of PPV conducted during the past several years, we have shown promising results in various types of cancers. 12,13,16,18,19 Table 1 shows the clinical responses in 500 advanced cancer patients who received PPV from October 2000 to October 2008. 16 The best clinical response assessed in 436 evaluable patients were partial response (PR) in 43 patients (10%), stable disease (SD) in 144 patients (33%) and progressive disease (PD) in 249 patients (57%), with a median overall survival of 9.9 mo.…”
Section: Lymphocyte Counts Increased Humoral Responses To the Vaccinmentioning
confidence: 99%
“…16 The best clinical response assessed in 436 evaluable patients were partial response (PR) in 43 patients (10%), stable disease (SD) in 144 patients (33%) and progressive disease (PD) in 249 patients (57%), with a median overall survival of 9.9 mo. Of note, as shown in Figure 2, 18 In addition, PPV was also conducted in an early phase clinical trial of patients with Figure 2. Progression-free and overall survival in patients with castration-resistant prostate cancer using personalized peptide vaccination.…”
Section: Lymphocyte Counts Increased Humoral Responses To the Vaccinmentioning
confidence: 99%